Building and Sustaining Diverse Functioning Networks Using Social Media and Digital Platforms to Improve Diversity and Inclusivity - Montgomery, Beronda L. (Frontiers in Digital Humanities, 2018)
There has long been a focus on building inclusion and diversity in the sciences through a range of efforts intended to increase representation and access. Despite expansive efforts supported by higher education institutions, funding agencies and others, a need persists to support broad participation and success. Digital platforms, including blogs and social media such as Twitter™, offer emergent paths for scientists to proactively build supportive communities, even where structural diversity or numerical representation of diverse groups remains low. Use of these platforms can range from community building, to proactive mentoring and advocacy, as well as more customary uses for supporting scholarly success of diverse individuals, including dissemination and accessible discussions of research. I discuss specific uses of social-media digital platforms for building and cultivating communities of underrepresented scholars and facilitating engagement around issues of broad concern to groups underrepresented in science and higher education. These uses include mentoring a nd support to promote equity, inclusion and diversity, promoting self-definition and personal agency, community building, and advocacy. I draw on published literature about using social media and digital platforms in higher education to build and cultivate “social networks” for connecting widely distributed individuals from underrepresented backgrounds to cultivate communities of interest, support and practice, including a focus on mentoring, sponsorship and advocacy. I highlight the power of Twitter™ and social media platforms to build and cultivate connections of individuals underrepresented in science and the academy and to offer meaningful means for mitigating local deficits related to low structural diversity and inequity.